2018
DOI: 10.4028/www.scientific.net/msf.930.374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solution Annealing Time on the Microstructure and Corrosion Resistance of Duplex Stainless Steel

Abstract: The formation of intermetallic phases during thermal treatments is a decisive point for the performance of duplex stainless steels, which may prevent the obtaining or provoke degradation of their properties. This paper presents an investigation on the corrosion resistance of duplex SAF 2205 steel as received and after solution annealing treatment. The objective was to evaluate the correlation between the solution annealing time, the resulting microstructural changes and the corrosion resistance of the steel th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Thus, DSS becomes more susceptible to the localized corrosion, for being sensitive to active dissolution and contributing to the degradation of passive film stability (Hilders et al, 2018, Jinlong et al, 2015, Lacerda et al, 2015, Li, Lo, Kwok, Sun & Lai, 2018, Mandal, 2016, Mohammed, Shrikrishna & Sathiya, 2016, Verma & Taiwade, 2017. Furthermore, the formation of α' causes a cross-stich displacement, leading to a decreased mobility of disagreements, leading to an increase in hardiness, in the yield point and mechanical resistance, besides reducing toughness and elongation (Appleton, 2019, Llorca-Isern, López-Jiménez, López-Luque, Biezma & Roca, 2016, Mandal, 2016, Marques, Silva & Santos, 2020, Mohammed et al, 2016, Paulraj & Garg, 2015, Rezende et al 2018, Rezende, Dainezi, Apolinario, Sousa & Mariano, 2019, Rivolta, Gerosa & Tavasci, 2018, Verma & Taiwade, 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, DSS becomes more susceptible to the localized corrosion, for being sensitive to active dissolution and contributing to the degradation of passive film stability (Hilders et al, 2018, Jinlong et al, 2015, Lacerda et al, 2015, Li, Lo, Kwok, Sun & Lai, 2018, Mandal, 2016, Mohammed, Shrikrishna & Sathiya, 2016, Verma & Taiwade, 2017. Furthermore, the formation of α' causes a cross-stich displacement, leading to a decreased mobility of disagreements, leading to an increase in hardiness, in the yield point and mechanical resistance, besides reducing toughness and elongation (Appleton, 2019, Llorca-Isern, López-Jiménez, López-Luque, Biezma & Roca, 2016, Mandal, 2016, Marques, Silva & Santos, 2020, Mohammed et al, 2016, Paulraj & Garg, 2015, Rezende et al 2018, Rezende, Dainezi, Apolinario, Sousa & Mariano, 2019, Rivolta, Gerosa & Tavasci, 2018, Verma & Taiwade, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Phase α' can be formed by two mechanisms, nucleation and growth, and spinodal decomposition of ferrite, depending (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i8.17369 on the chemical composition of the ferrite phase and the temperature of the treatment. Both mechanisms occur to reduce the Gibbs free energy of the system and, consequently, promote a thermodynamically more stable state (Appleton, 2019, Llorca-Isern et al, 2016, Marques et al, 2020, Mohammed et al, 2016, Paulraj & Garg, 2015, Rezende et al 2018, Rivolta et al, 2018, Verma & Taiwade, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…A higher volume fraction of austenite than ferrite is observed for the FP1 sample, the fact seemed to be associated with the reversion mechanism from deformation-induced α'-martensite to austenite. Microstructural changes inside the austenitic lamellae are related to austenite-ferrite transformation 16 . Recrystallization of the ferrite progressed during annealing at 1000 °C so that the ferrite lamellae became larger.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…On the other hand, the instability of the ferrite phase, due to improper heat treatment temperature, may cause the precipitation of deleterious secondary phases, such as the sigma phase in duplex stainless steels, which causes the Cr and Mo elements to be depleted in the regions adjacent to the matrix due to their consumption in solid solution, reducing the corrosion resistance and mechanical properties [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Improper annealing temperature promotes formation of intermetallic precipitation which depends on presence of Cr, Mo. Furthermore, several studies showed the Nearby zone of the Sigma phase depleted of Mo, Cr, whereas sigma phase enriched with Cr, Mo, and presence of intermetallic phases make duplex stainless steel was prone to Embrittlement [4], and consequently low corrosion resistance and deteriorated mechanical properties [9], [10] [11], [12] [13].…”
Section: Introductionmentioning
confidence: 99%